An Effect Of Transformational Leadership Style And Organ-izational Climate On Employee Performance At PT. Se-jahtera Mandiri - Elsa Nurul Anggelina; Rifky Budi Setiawan; Fitra Arlina Naution (Sean Institute, 2024)
This research discussed an impact of transformational leadership style and organiza-tional climate on employee performance at PT. Sejahtera Mandiri. It explores how a lead-ership approach that inspires, motivates, and supports employee development, combined with a positive work environment, influences individual and organizational effectiveness. The findings reveal a significant correlation between transformational leadership, a con-ducive organizational climate, and improved employee performance, underscoring the importance of leadership practices and workplace atmosphere in achieving optimal productivity and engagement levels.